Meningkatkan Literasi Matematis Siswa MTs/SMP Dengan Menerapkan Pembelajaran CORE - Nasrulloh, Muhammad Farid; Putri, Sania Eliza; Satiti, Wisnu Siwi; Khotimah, Khusnul (JoEMS (Journal of Education and Management Studies), 2023)
The purpose of this research was to determine the effectiveness of the CORE learning model in improving mathematical literacy of students grade 8th. This research uses pre-experimental design research method with the type of method is one-group pretest-posttest design, the research approach used is quantitative. The research instrument uses tests and non-tests. Test instruments in the form of pretest and post-test were used to measure students' mathematical literacy before and after applying CORE learning model. The non-test instrument used was an interview with a grade 8thmathematics teacher to determine the implementation of learning carried out in the classroom. The subject is class VIII D MTs Salafiyah Syafiiyah Bandung. The data analysis technique used is the paired sample t test. Based on the calculation of the paired sample t test, the resulting significance value is 0.000. The significance value shows 0.000 < 0.05 error level, so it can be concluded that Ha is accepted. This acceptance of Ha means that there are differences in the level of mathematical literacy of grade 8thMTs Salafiyah Syafiiyah Bandung before and after applying CORE learning model. This means that the CORE learning model is effective for improving students' mathematical literacy.